Internal organizational factors influencing the adoption of sustainable solid waste management in Zanzibar hotels: A qualitative multiple-case study - Malik Omar Mohamed; Bukaza Chachage; Ladislaus Batinoluho; Adriana Budeanu; Peter Furu (School of Tourism, Universitas Ciputra Surabaya, 2026)
Solid waste generation from the hospitality industry poses a significant global sustainability challenge for tourist destinations, including Zanzibar. The existing literature presents conflicting findings on the internal factors influencing hotels' adoption of sustainable solid waste management (SSWM) practices. Also, the majority of studies focus on broader environmental sustainability, neglecting SSWM. This study addresses this gap by investigating the internal factors affecting SSWM adoption in Zanzibar hotels, utilizing organizational theory as a lens. The study employed a qualitative multiple-case design, involving 14 hotels and 45 respondents recruited through snowball and purposive sampling. Primary data were gathered through semi-structured interviews, observations, and document reviews, and were analysed thematically using MAXQDA software. The study found that organizational learning, leadership support, resources, and structure significantly influence SSWM practices in five out of 14 hotels. Additionally, employee motivation does not impact SSWM adoption in these hotels. Interviews with managers and department leaders revealed two unexpected factors: organizational adaptability and employee teamwork as key factors in SSWM adoption. The majority of three- to four-star hotels involved in this study struggled to implement sustainable waste management due to inadequate leadership support, limited organizational learning, insufficient resources, and the absence of a clear waste management policy and expertise. This study advances existing knowledge by providing empirical evidence of the importance of organizational structure and leadership support in advancing sustainable waste management practices within the hospitality industry.